A negative electrode active material and a lithium ion battery using the same
By introducing silicon grains into the negative electrode active material of lithium-ion batteries and processing them through specific processes, the problem of the negative electrode materials prone to breaking and crushing during circulation in the prior art is solved, and higher gram capacity and structural stability are achieved extends the battery cycle life.
Patent Information
- Application Number
- CN202410315953.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2023-10-26
- Filing Date
- 2024-03-19
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-03-19
AI Technical Summary
The negative electrode active materials of existing lithium-ion batteries are prone to rupture and shatter during the cycle charging and discharge process, resulting in structural collapse, powderization and irreversible consumption, thereby reducing electrochemical properties.
Graphite negative electrode material is used to match silicon grains, with a silicon content of no less than 2500ppm. Through specific heat treatment and spheroidization treatment processes, silicon grains embedded in the inter-graphite layer structure are formed to enhance the structural stability of the negative electrode active material.
The gram capacity of the negative electrode active material is significantly improved, and the structural stability is maintained during the cycle charging and discharge process is maintained, extending the cycle life and electrochemical performance of lithium-ion batteries.
Smart Images

Figure BDA0004748967850000131 
Figure BDA0004748967850000141 
Figure BDA0004748967850000171
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of secondary batteries, and in particular, relates to a negative electrode active material and a lithium ion battery using the negative electrode active material. Background Art
[0002] Lithium-ion batteries have the characteristics of high voltage, no memory effect, and high energy density. They have been widely used in portable appliances such as smart phones and laptops. Existing lithium-ion batteries mainly use graphite materials as negative electrode active materials. The theoretical capacity of graphite is 372mAh / g. Among them, natural graphite has an actual gram capacity of more than 360mAh / g due to its high crystallinity, which is very close to the theoretical capacity of graphite. However, with the development of science and technology, graphite materials are difficult to meet the increasingly urgent high energy needs. Elemental silicon has a higher theoretical gram capacity (4200mAh / g). Based on this, the gram capacity of graphite materials can be increased by introducing elemental silicon into graphite materials. However, when graphite materials containing elemental silicon are used as negative electrode active materials in lithium-ion batteries, the particles of elemental silicon are easily broken and crushed as the charge and discharge cycles proceed, causing the structure of the negative electrode active materials to collapse, pulverize, and even fall off the current collector, exposing more interfaces of the negative electrode active materials in contact with the electrolyte. The irreversible consumption of the negative electrode active materials caused by side reactions between the negative electrode active materials and the electrolyte is aggravated, resulting in a sharp decline in the electrochemical performance of the negative electrode active materials and the lithium-ion batteries using them. Summary of the invention
[0003] The object of the present invention is to provide a negative electrode active material and a lithium ion battery using the same, so as to improve the gram capacity of the graphite negative electrode active material and maintain good cycle performance of the graphite negative electrode active material and the lithium ion battery using the same.
[0004] According to a first aspect of the present invention, there is provided a negative electrode active material, comprising a graphite negative electrode material, wherein the graphite negative electrode material comprises graphite and silicon grains, wherein the silicon content in the negative electrode active material is not less than 2500 ppm; and a button cell made of the negative electrode active material has a voltage dQ / dV differential curve with a peak intensity of <600 mAh·g in the range of 0.4 to 0.5 V. -1 ·V -1 The voltage dQ / dV differential curve is obtained by charging and discharging the button cell at a rate of 0.05C at 20-30°C, and obtaining the voltage dQ / dV differential capacity curve from the charging curve of the fifth cycle. Due to the use of silicon grains and graphite, the negative electrode active material provided by the present invention has a significantly improved gram capacity compared to general graphite negative electrode materials. Silicon grains are easily generated Li due to lithiation during the lithium ion cycle charge and discharge process. 15 Si4, Li15 The more Si4 is generated, the more uneven internal stress accumulates in the negative electrode active material, which makes the silicon-containing negative electrode active material prone to cracking and crushing. However, the negative electrode active material provided by the present invention participates in the process of lithium-ion battery cycle charge and discharge. 15 The amount of Si4 generated is small, which makes the structural stability of the negative electrode active material better, and thus has good cycle characteristics.
[0005] According to a second aspect of the present invention, a lithium ion battery is provided, comprising a positive electrode sheet and a negative electrode sheet, wherein the negative electrode active material layer of the negative electrode sheet contains the negative electrode active material as described above. The negative electrode active material used in the lithium ion battery of the present invention has a high gram capacity, a sufficiently high first efficiency and good structural stability, so that the lithium battery exhibits excellent electrochemical performance and cycle stability. DETAILED DESCRIPTION
[0006] According to a first aspect of the present invention, there is provided a negative electrode active material, comprising a graphite negative electrode material, wherein the graphite negative electrode material comprises graphite and silicon grains, wherein the silicon content in the negative electrode active material is not less than 2500 ppm; and a button cell made of the negative electrode active material has a voltage dQ / dV differential curve with a peak intensity of <600 mAh·g in the range of 0.4 to 0.5 V. -1 ·V -1 The voltage dQ / dV differential curve is obtained by charging and discharging the button cell at a rate of 0.05C at 20-30°C, and obtaining the voltage dQ / dV differential capacity curve from the charging curve of the fifth cycle. Due to the use of silicon grains and graphite, the negative electrode active material provided by the present invention has a significantly improved gram capacity compared to general graphite negative electrode materials. Silicon grains are easily generated Li due to lithiation during the lithium ion cycle charge and discharge process. 15 Si4, Li 15 The more Si4 is generated, the more uneven internal stress accumulates in the negative electrode active material, which makes the silicon-containing negative electrode active material prone to cracking and crushing. However, the negative electrode active material provided by the present invention participates in the process of lithium-ion battery cycle charge and discharge. 15 The amount of Si4 generated is small, which makes the structural stability of the negative electrode active material better, and thus has good cycle characteristics.
[0007] Preferably, in the voltage dQ / dV differential curve, the peak intensity in the range of 0.4 to 0.5 V is less than 300 mAh·g -1 ·V -1 The negative electrode active material having the above characteristics can achieve better cycle performance.
[0008] Preferably, the particle size of the silicon crystal is less than 50 nm. The peak intensity of the characteristic peak of the dQ / dV curve of the negative electrode active material corresponding to the button cell measured in the range of 0.4V to 0.5V does not exceed 600mAh·g -1 ·V -1 Under the premise of this, if the particle size of the silicon grains can be controlled within the above range, it will be beneficial to increase the silicon content in the negative electrode active material, thereby helping to increase the gram capacity of the negative electrode active material. At the same time, the particle size of the silicon grains within the above range makes the structural stability of the negative electrode active material better.
[0009] Preferably, the particle size of the silicon grains is less than 25 nm.
[0010] Preferably, the silicon content in the negative electrode active material is 2500-30000 ppm. The peak intensity of the characteristic peak of the dQ / dV curve of the negative electrode active material corresponding to the button cell measured in the range of 0.4V-0.5V does not exceed 600mAh·g -1 ·V -1 Under the premise of controlling the silicon content in the negative electrode active material within the above range, even if the particle size of the silicon grains is appropriately increased, the structural stability of the negative electrode active material can be maintained well, thereby eliminating the need for complex or costly processing to limit the increase of silicon grains.
[0011] Preferably, in the negative electrode active material, the silicon content is 2500 to 15000 ppm.
[0012] Preferably, the graphite negative electrode material comprises natural graphite.
[0013] Preferably, in the graphite negative electrode material, at least a portion of the silicon grains are embedded in the interlayer structure of the graphite. During the charge and discharge cycle of the lithium-ion battery, the graphite around the silicon grains can have a certain binding effect on the expanded silicon grains, thereby preventing the expanded silicon grains from falling off the negative electrode active material, thereby achieving the effect of avoiding cycle jump.
[0014] Preferably, at a charging voltage of 5mV to 2V, the charge capacity of the negative electrode active material is >372mAh·g -1 .
[0015] According to a second aspect of the present invention, a lithium ion battery is provided, comprising a positive electrode sheet and a negative electrode sheet, wherein the negative electrode active material layer of the negative electrode sheet contains the negative electrode active material as described above. The negative electrode active material used in the lithium ion battery of the present invention has a high gram capacity, a sufficiently high first efficiency and good structural stability, so that the lithium battery exhibits excellent electrochemical performance and cycle stability.
[0016] In order to enable those skilled in the art to better understand the solutions of the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only embodiments of a part of the present invention, rather than all embodiments.
[0017] Example 1
[0018] In this embodiment, the negative electrode active material is prepared according to the following method:
[0019] S1. Take 10kg flake natural graphite (D 50 =55.4μm, Si content =39742ppm) and 0.1kg charcoal (D 50 =1μm) to the air vortex micronizer, adjust the classifier wheel speed to 4500r / min, the spheroidizing wheel speed to 5000r / min, and the air volume to 3m 3 / min, work for 2 hours, slowly discharge the material, and obtain a spherical precursor (D 50 is 11.2μm).
[0020] S2. The spherical precursor and 0.8 kg of asphalt are placed in a VC mixer and mixed evenly, and then the material is taken to a box-type carbonization furnace for heat treatment. The specific operation of the heat treatment is: heating to 500°C at a heating rate of 5°C / min, keeping a constant temperature at 500°C for 2 hours, and then naturally cooling to room temperature and taking out to obtain a semi-finished product.
[0021] S3. The semi-finished product is then transferred to a low-temperature graphitization furnace, argon gas is introduced, and the temperature is first increased to 1200°C at a rate of 10°C / min, and then increased to 1900°C at a rate of 5°C / min. After being kept at 1900°C for 3 hours, it is naturally cooled to room temperature and then taken out. After being broken up and sieved, a negative electrode active material containing silicon grains and natural graphite is obtained.
[0022] The negative electrode active material prepared in this embodiment includes silicon grains, natural graphite and amorphous carbon. In the negative electrode active material prepared in this embodiment, the natural graphite is spherical. Since the spherical natural graphite is curled from the flaky natural graphite in the raw material, the spherical natural graphite retains a lamellar structure inside, and the silicon grains are embedded in the lamellar structure of the spherical natural graphite. The amorphous carbon in the finished negative electrode active material forms an outer coating layer covering the outside of the natural graphite.
[0023] Example 2
[0024] In this embodiment, the negative electrode active material is prepared according to the following method:
[0025] S1. Take 10kg flake natural graphite (D 50=57.2μm, Si content = 31020ppm) and 0.08kg blue carbon (D 50 =1μm) to the air vortex micronizer, adjust the classifier wheel speed to 4000r / min, the spheroidizing wheel speed to 4500r / min, and the air volume to 3m 3 / min, work for 2 hours, slowly discharge the material, and obtain a spherical precursor (D 50 is 11.5μm).
[0026] S2. The spherical precursor and 0.8 kg of asphalt are placed in a VC mixer and mixed evenly, and then the material is taken to a box-type carbonization furnace for heat treatment. The specific operation of the heat treatment is: heating to 500°C at a heating rate of 5°C / min, keeping a constant temperature at 500°C for 2 hours, and then naturally cooling to room temperature and taking out to obtain a semi-finished product.
[0027] S3. The semi-finished product is then transferred to a low-temperature graphitization furnace, argon gas is introduced, and the temperature is first increased to 1200°C at a rate of 10°C / min, and then increased to 1600°C at a rate of 5°C / min. After being kept at 1600°C for 3 hours, it is naturally cooled to room temperature and then taken out. After being broken up and sieved, a negative electrode active material containing silicon grains and natural graphite is obtained.
[0028] The negative electrode active material prepared in this embodiment includes silicon grains, natural graphite and amorphous carbon. The negative electrode active material thus prepared is observed and analyzed by scanning electron microscopy and transmission electron microscopy. It can be seen that in the negative electrode active material prepared in this embodiment, the natural graphite is spherical. Since the spherical natural graphite is curled from the flaky natural graphite in the raw material, the spherical natural graphite retains a lamellar structure inside, and the silicon grains are embedded in the lamellar structure of the spherical natural graphite. The amorphous carbon in the finished negative electrode active material forms an outer coating layer covering the outside of the natural graphite.
[0029] Example 3
[0030] In this embodiment, the negative electrode active material is prepared according to the following method:
[0031] S1. Take 10kg flake natural graphite (D 50 =55.4μm, Si content =39742ppm) to the air vortex micronizer, adjust the classifier wheel speed to 4500r / min, the spheroidizing wheel speed to 5000r / min, and the air volume to 3m 3 / min, work for 2 hours, slowly discharge the material, and obtain a spherical precursor (D 50 is 11.4μm).
[0032] S2. The spherical precursor and 0.8 kg of asphalt are placed in a VC mixer and mixed evenly, and then the material is taken to a box-type carbonization furnace for heat treatment. The specific operation of the heat treatment is: heating to 500°C at a heating rate of 5°C / min, keeping a constant temperature at 500°C for 2 hours, and then naturally cooling to room temperature and taking out to obtain a semi-finished product.
[0033] S3. The semi-finished product is then transferred to a low-temperature graphitization furnace, argon gas is introduced, and the temperature is first increased to 1200°C at a rate of 10°C / min, and then increased to 1600°C at a rate of 5°C / min. After being kept at 1600°C for 6 hours, it is naturally cooled to room temperature and then taken out. After being broken up and sieved, a negative electrode active material containing silicon grains and natural graphite is obtained.
[0034] The negative electrode active material prepared in this embodiment includes silicon grains, natural graphite and amorphous carbon. In the negative electrode active material prepared in this embodiment, the natural graphite is spherical. Since the spherical natural graphite is curled from the flaky natural graphite in the raw material, the spherical natural graphite retains a lamellar structure inside, and the silicon grains are embedded in the lamellar structure of the spherical natural graphite. The amorphous carbon in the finished negative electrode active material forms an outer coating layer covering the outside of the natural graphite.
[0035] Example 4
[0036] In this embodiment, the negative electrode active material is prepared according to the following method:
[0037] S1. Take 10kg flake natural graphite (D 50 =57.2μm, Si content =31020ppm) to the air vortex micronizer, adjust the classifier wheel speed to 4000r / min, the spheroidizing wheel speed to 4500r / min, and the air volume to 3m 3 / min, work for 2 hours, slowly discharge the material, and obtain a spherical precursor (D 50 is 11.5μm).
[0038] S2. The spherical precursor and 0.8 kg of asphalt are placed in a VC mixer and mixed evenly, and then the material is taken to a box-type carbonization furnace for heat treatment. The specific operation of the heat treatment is: heating to 500°C at a heating rate of 5°C / min, keeping a constant temperature at 500°C for 2 hours, and then naturally cooling to room temperature and taking out to obtain a semi-finished product.
[0039] S2. The semi-finished product is then transferred to a low-temperature graphitization furnace, argon gas is introduced, and the temperature is first increased to 1200°C at a rate of 10°C / min, and then increased to 1600°C at a rate of 5°C / min. After being kept at 1600°C for 6 hours, it is naturally cooled to room temperature and then taken out. After being broken up and sieved, a negative electrode active material containing silicon grains and natural graphite is obtained.
[0040] The negative electrode active material prepared in this embodiment includes silicon grains, natural graphite and amorphous carbon. In the negative electrode active material prepared in this embodiment, the natural graphite is spherical. Since the spherical natural graphite is curled from the flaky natural graphite in the raw material, the spherical natural graphite retains a lamellar structure inside, and the silicon grains are embedded in the lamellar structure of the spherical natural graphite. The amorphous carbon in the finished negative electrode active material forms an outer coating layer covering the outside of the natural graphite.
[0041] Example 5
[0042] In this embodiment, the negative electrode active material is prepared according to the following method:
[0043] S1. Use hydrofluoric acid to wash the flake natural graphite with weak acid, take 10kg of the flake natural graphite (D 50 =54.5μm, Si content =3189ppm) to the air vortex micronizer, adjust the classifier wheel speed to 3000r / min, the spheroidizer wheel speed to 3500r / min, and the air volume to 3m 3 / min, work for 2 hours, slowly discharge the material, and obtain a spherical precursor (D 50 is 11.5μm).
[0044] S2. The spherical precursor and 0.8 kg of asphalt are placed in a VC mixer and mixed evenly, and then the material is taken to a box-type carbonization furnace for heat treatment. The specific operation of the heat treatment is: heating to 1000°C at a heating rate of 5°C / min, keeping a constant temperature at 1000°C for 2 hours, and then naturally cooling to room temperature and taking out to obtain a semi-finished product.
[0045] S3. The semi-finished product is then transferred to a high-frequency induction heating furnace and argon gas is introduced. The excitation frequency and input power of the high-frequency induction heating furnace are set to 75KHz and 45KW respectively. The product is operated for 2 hours. After naturally cooling to room temperature, it is taken out and broken up and sieved to obtain a negative electrode active material containing silicon grains and natural graphite.
[0046] The negative electrode active material prepared in this embodiment includes silicon grains, natural graphite and amorphous carbon. In the negative electrode active material prepared in this embodiment, the natural graphite is spherical. Since the spherical natural graphite is curled from the flaky natural graphite in the raw material, the spherical natural graphite retains a lamellar structure inside, and the silicon grains are embedded in the lamellar structure of the spherical natural graphite. The amorphous carbon in the finished negative electrode active material forms an outer coating layer covering the outside of the natural graphite.
[0047] Example 6
[0048] In this embodiment, the negative electrode active material is prepared according to the following method:
[0049] S1. Take 10kg flake natural graphite (D 50 =54.1μm, Si content = 15794ppm) to the air vortex micronizer, adjust the classifier wheel speed to 3500r / min, the spheroidizer wheel speed to 4000r / min, and the air volume to 3m 3 / min, work for 2 hours, slowly discharge the material, and obtain a spherical precursor (D 50 is 11.7μm).
[0050] S2. The spherical precursor and 0.8 kg of asphalt are placed in a VC mixer and mixed evenly, and then the material is taken to a box-type carbonization furnace for heat treatment. The specific operation of the heat treatment is: heating to 1000°C at a heating rate of 5°C / min, keeping a constant temperature at 1000°C for 2 hours, and then naturally cooling to room temperature and taking out to obtain a semi-finished product.
[0051] S3. The semi-finished product is then transferred to a microwave heating furnace, argon gas is introduced, the microwave frequency and input power of the microwave heating furnace are set to 2450 MHz and 1.5 kW respectively, and the product is operated for 2 hours. After naturally cooling to room temperature, the product is taken out, broken up and sieved to obtain a negative electrode active material containing silicon grains and natural graphite.
[0052] The negative electrode active material prepared in this embodiment includes silicon grains, natural graphite and amorphous carbon. In the negative electrode active material prepared in this embodiment, the natural graphite is spherical. Since the spherical natural graphite is curled from the flaky natural graphite in the raw material, the spherical natural graphite retains a lamellar structure inside, and the silicon grains are embedded in the lamellar structure of the spherical natural graphite. The amorphous carbon in the finished negative electrode active material forms an outer coating layer covering the outside of the natural graphite.
[0053] Example 7
[0054] In this embodiment, the negative electrode active material is prepared according to the following method:
[0055] S1. Pickling the flake natural graphite with nitric acid, taking 10kg of the flake natural graphite (D 50 =54.1μm, Si content is 0) to the air vortex micronizer, adjust the speed of the classifier to 3000r / min, the speed of the spheroidizing wheel to 3500r / min, and the air volume to 3m 3 / min, work for 2 hours, slowly discharge the material, and obtain a spherical precursor (D 50 is 11.8μm).
[0056] S2. Disperse 150 g of nano-silicon particles with a grain size of 20 nm evenly into 1 L of ethanol solution, and then place the mixed solution and 10 kg of spherical precursor in a ball mill for ball milling (340 r / min, ball milling for 6 hours), so that the silicon grains are coated on the outside of the spherical precursor, which is used as a semi-finished product.
[0057] S3. The semi-finished product and 0.8 kg of asphalt are placed in a VC mixer and mixed evenly, and then the material is taken into a box-type carbonization furnace for heat treatment. The specific operation of the heat treatment is: heating to 1250°C at a heating rate of 10°C / min, keeping a constant temperature at 1250°C for 4 hours, cooling naturally to room temperature and then taking it out, breaking it up and screening it to obtain a negative electrode active material containing silicon grains and natural graphite.
[0058] The negative electrode active material prepared in this embodiment includes silicon grains, natural graphite and amorphous carbon. In the negative electrode active material prepared in this embodiment, the natural graphite is spherical. Since the spherical natural graphite is curled from the flake natural graphite in the raw material, the spherical natural graphite retains the lamellar structure. However, it is worth noting that in the finished negative electrode active material prepared in this embodiment, the silicon grains are all attached to the outer surface of the spherical natural graphite without entering its lamellar structure. The reason for the formation of this structure is that in the process of preparing the negative electrode active material in this embodiment, the silicon grains are introduced into the reaction system after the spherical precursor of natural graphite is prepared. As described in S2 of this embodiment, the silicon grains will be coated on the outside of the spherical precursor, so that in the final finished negative electrode active material, the silicon grains are only distributed on the outer surface of the spherical natural graphite without entering its internal lamellar structure. In addition, the amorphous carbon in the finished negative electrode active material forms an outer coating layer covering the natural graphite and the silicon grains.
[0059] Comparative Example 1
[0060] This comparative example prepared the negative electrode active material according to the following method:
[0061] S1. Pickling the flake natural graphite with nitric acid, taking 10kg of the flake natural graphite (D 50 =54.1μm, Si content is 0) is placed in the VC mixture and mixed evenly, then the material is taken into the air flow vortex micro powder machine, the speed of the classifier wheel is adjusted to 3500r / min, the speed of the spheroidizing wheel is adjusted to 4000r / min, and the air volume is adjusted to 3m 3 / min, work for 2 hours, slowly discharge the material, and obtain a spherical precursor (D 50 is 11.7μm).
[0062] S2. The spherical precursor and 0.8 kg of asphalt are placed in a VC mixer and mixed evenly, and then the material is taken to an Acheson graphitization furnace protected by nitrogen for heat treatment. The specific operation of the heat treatment is: heating to 1250°C at a heating rate of 10°C / min, and then heating to 3000°C at a heating rate of 5°C / min. After keeping constant at 3000°C for 4 hours, naturally cool to room temperature, take out, break up and sieve, and use the powder obtained as the negative electrode active material of this comparative example.
[0063] The negative electrode active material prepared in this comparative example includes natural graphite and amorphous carbon, and does not contain silicon grains. In the negative electrode active material prepared in this comparative example, the natural graphite is spherical. Since the spherical natural graphite is curled from the flaky natural graphite in the raw material, the spherical natural graphite retains a lamellar structure inside, and the amorphous carbon in the finished negative electrode active material forms an outer coating layer covering the outside of the natural graphite.
[0064] Comparative Example 2
[0065] This comparative example prepared the negative electrode active material according to the following method:
[0066] S1. Take flake natural graphite (D 50 =56.5μm, Si content =51780ppm) and 0.12kg charcoal (D 50 =1μm) to the air vortex micronizer, adjust the classifier wheel speed to 5500r / min, the spheroidizer wheel speed to 6000r / min, and the air volume to 4m 3 / min, work for 2 hours, slowly discharge the material, and obtain a spherical precursor (D 50 is 11.8μm).
[0067] S2. The spherical precursor and 0.8 kg of asphalt are placed in a VC mixer and mixed evenly, and then the material is taken to a box-type carbonization furnace for heat treatment. The specific operation of the heat treatment is: heating to 500°C at a heating rate of 5°C / min, keeping a constant temperature at 500°C for 2 hours, and then naturally cooling to room temperature and taking out to obtain a semi-finished product.
[0068] S3. The semi-finished product is then transferred to a low-temperature graphitization furnace, argon gas is introduced, and the temperature is first increased to 1200°C at a rate of 10°C / min, and then increased to 1900°C at a rate of 5°C / min. After being kept at 1900°C for 6 hours, it is naturally cooled to room temperature and then taken out. After being broken up and sieved, a negative electrode active material containing silicon grains and natural graphite is obtained.
[0069] The negative electrode active material prepared in this comparative example includes silicon grains, natural graphite and amorphous carbon. In the negative electrode active material prepared in this comparative example, the natural graphite is spherical. Since the spherical natural graphite is curled from the flaky natural graphite in the raw material, the spherical natural graphite retains a lamellar structure inside, and the silicon grains are embedded in the lamellar structure of the spherical natural graphite. The amorphous carbon in the finished negative electrode active material forms an outer coating layer covering the outside of the natural graphite.
[0070] Comparative Example 3
[0071] This comparative example prepared the negative electrode active material according to the following method:
[0072] S1. Take flake natural graphite (D 50 =56.5μm, Si content =51780ppm) to the air vortex micronizer, adjust the classifier wheel speed to 5500r / min, the spheroidizing wheel speed to 6000r / min, and the air volume to 4m 3 / min, work for 2 hours, slowly discharge the material, and obtain a spherical precursor (D 50 is 11.8μm).
[0073] S2. The spherical precursor and 0.8 kg of asphalt are placed in a VC mixer and mixed evenly, and then the material is taken to a box-type carbonization furnace for heat treatment. The specific operation of the heat treatment is: heating to 1000°C at a heating rate of 5°C / min, keeping a constant temperature at 1000°C for 2 hours, and then naturally cooling to room temperature and taking out to obtain a semi-finished product.
[0074] S3. The semi-finished product is then transferred to a microwave heating furnace, argon gas is introduced, the microwave frequency and input power of the microwave heating furnace are set to 2450 MHz and 1.5 kW respectively, and the product is operated for 2.5 hours. After naturally cooling to room temperature, the product is taken out, broken up and sieved to obtain a negative electrode active material containing silicon grains and natural graphite.
[0075] The negative electrode active material prepared in this comparative example includes silicon grains, natural graphite and amorphous carbon. In the negative electrode active material prepared in this comparative example, the natural graphite is spherical. Since the spherical natural graphite is curled from the flaky natural graphite in the raw material, the spherical natural graphite retains a lamellar structure inside, and the silicon grains are embedded in the lamellar structure of the spherical natural graphite. The amorphous carbon in the finished negative electrode active material forms an outer coating layer covering the outside of the natural graphite.
[0076] Comparative Example 4
[0077] This comparative example prepared the negative electrode active material according to the following method:
[0078] S1. This embodiment uses the flake natural graphite obtained by weak pickling treatment in S1 of Example 5 as raw material, and takes 10kg of the above-mentioned flake natural graphite (D 50 =54.5μm, Si content = 3189ppm) and 0.05kg blue carbon (D 50 =1μm) to the air vortex micronizer, adjust the speed of the classifier to 3000r / min, the speed of the spheroidizing wheel to 3500r / min, and the air volume to 3m 3 / min, work for 2 hours, slowly discharge the material, and obtain a spherical precursor (D 50 is 11.4μm).
[0079] S2. The spherical precursor and 0.8 kg of asphalt are placed in a VC mixer and mixed evenly, and then the material is taken to a box-type carbonization furnace for heat treatment. The specific operation of the heat treatment is: heating to 500°C at a heating rate of 5°C / min, keeping a constant temperature at 500°C for 2 hours, and then naturally cooling to room temperature and taking out to obtain a semi-finished product.
[0080] S3. The semi-finished product is then transferred to a low-temperature graphitization furnace, argon gas is introduced, and the temperature is first increased to 1200°C at a rate of 10°C / min, and then increased to 1600°C at a rate of 5°C / min. After being kept at 1600°C for 6 hours, it is naturally cooled to room temperature and then taken out. After being broken up and sieved, a negative electrode active material containing silicon grains and natural graphite is obtained.
[0081] The negative electrode active material prepared in this comparative example includes silicon grains, natural graphite and amorphous carbon. The negative electrode active material thus prepared is observed and analyzed by scanning electron microscopy and transmission electron microscopy. It can be seen that in the negative electrode active material prepared in this comparative example, the natural graphite is spherical. Since the spherical natural graphite is curled from the flaky natural graphite in the raw material, the spherical natural graphite retains a lamellar structure inside, and the silicon grains are embedded in the lamellar structure of the spherical natural graphite. The amorphous carbon in the finished negative electrode active material forms an outer coating layer covering the outside of the natural graphite.
[0082] Example 8
[0083] In this embodiment, button batteries were prepared using the negative electrode active materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 in the following manner.
[0084] 1. Preparation of the small circle of the electrode
[0085] The negative electrode active materials for preparing lithium ion batteries provided in Examples 1 to 7 and Comparative Examples 1 to 4 are respectively mixed with a conductive agent acetylene black, a thickener CMC, and a binder SBR in a mass ratio of negative electrode active material: acetylene black: CMC: SBR = 94.5:1.5:1.5:2.5, and deionized water as a solvent is added to the resulting mixture. The resulting slurry is added to a vacuum mixer, and the slurry is stirred until the system is uniform under the action of the vacuum mixer to obtain a pole piece slurry; the pole piece slurry is evenly coated on one surface of a copper foil, and after drying at room temperature, it is cold pressed and cut to obtain a pole piece small circle of ф14 mm.
[0086] 2. Preparation of Electrolyte
[0087] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a LiPF6 concentration of 1 mol / L.
[0088] 3. Selection of isolation film
[0089] A polyethylene film is selected as the separating film and is cut into small diaphragm circles of ф19mm.
[0090] 4. Preparation of button cells
[0091] First, the pole piece circle prepared above is dried in a vacuum box at -1.0MPa and 80℃ for 8 hours, the pole piece circle is weighed, and the mass of the active material on the pole piece circle is calculated. The pole piece circle is used as the positive electrode of the button battery, and the lithium sheet is used as the negative electrode of the button battery. Subsequently, the components and materials used to assemble the button battery are transferred to the glove box and the above components and materials are assembled in the order of negative electrode shell, gasket, lithium sheet, electrolyte, diaphragm, electrolyte, pole piece circle, positive electrode shell to obtain a button battery.
[0092] Test Example 1
[0093] 1. Test subjects
[0094] This test example uses the button cell prepared in Example 8 as the test object.
[0095] 2. Test items
[0096] (1) Power-off test
[0097] At 25°C, the test object is subjected to a button test according to the following procedure: the test object is set aside for 12 hours, the test object is discharged to 5mV at a rate of 0.1C, and then the test object is discharged to 5mV at a rate of 0.05C for 10 minutes, and then the test object is discharged to 5mV at a rate of 0.01C for 10 minutes, and then the test object is discharged to 5mV at a current of 0.01mA for 10 minutes, and finally the test object is charged to 2V at a constant current of 0.1C, and the test object is terminated after being set aside for 10 minutes, and the gram capacity and first efficiency of the negative electrode active material contained in the button battery as the test object are recorded. The above method is repeated for 5 cycles, and the dQ / dV curve is made with the charging curve of the 5th cycle.
[0098] (2) Silicon grain size test
[0099] The size of silicon grains in the negative electrode active material is tested by X-ray diffractometer (XRD). The test principle is as follows: a very small grain in the positive space can be regarded as a sphere in the reciprocal space, and the peak width of its diffraction peak is very wide, while a sufficiently large grain in the positive space is a point in the reciprocal space, and the corresponding diffraction peak has a very narrow peak width. The change in grain size can be reflected in the peak width of the diffraction peak. Therefore, the particle size of silicon grains in the tested sample (negative electrode active material) can be calculated using the Scherrel formula: D = Kλ / (COSθ*β 1 / 2 )(suitable for grain range of 10nm~100nm), where D is the thickness along the vertical direction of the crystal plane, which can be considered as the grain size of silicon grains, K is the diffraction Scherrel constant, and the value of K is 0.89; λ is the wavelength of X-rays, β 1 / 2 is the half-height width of the diffraction peak, in radians; θ is the Bragg diffraction angle.
[0100] (3) Silicon content test
[0101] The silicon content in the negative electrode active material was tested using an inductively coupled plasma spectrometer (ICP). Take 0.5 g of the negative electrode active material and digest it using a microwave digester until the negative electrode active material sample is completely digested to obtain a digestion product. And 6 mL of hydrofluoric acid and 2 mL of nitric acid are mixed to obtain a mixed acid solution. The temperature of the mixed acid solution is restored to room temperature, the mixed acid solution and the digestion product are mixed, and the resulting mixed solution is poured into a 100 mL constant volume flask, and deionized water is added to the constant volume flask to make it constant. Finally, the silicon content of the sample solution after constant volume is tested using an ICP test (Agilent 5110).
[0102] 3. Test results
[0103] The test results of this test case are shown in Table 1.
[0104] Among the negative electrode active materials used in the test objects, only the negative electrode active material provided by Comparative Example 1 does not contain silicon grains. In the process of preparing the negative electrode active material, the natural graphite is graphitized at 3000°C, and the crystallinity of the coated carbon layer is improved, but the capacity of the natural graphite is still less than the theoretical gram capacity of 372 mAh / g, and for highly crystalline natural graphite, the closer to the theoretical capacity, the more difficult it is to increase the capacity. Compared with the negative electrode active material prepared in Comparative Example 1, the negative electrode active materials obtained by introducing silicon grains into natural graphite in Examples 1 to 7 and Comparative Examples 2 to 4 all have improved corresponding measured gram capacities, among which the corresponding measured gram capacities of the negative electrode active materials prepared in Examples 1 to 7 all exceed the theoretical gram capacity of natural graphite of 372 mAh·g -1 Although the introduction of silicon crystals will slightly reduce the first efficiency of the negative electrode active material, the first efficiency of the negative electrode active materials prepared in Examples 1 to 7 can still reach a relatively high level and meet the requirements of practical applications.
[0105] In the dQ / dV curve obtained in this test example, the dQ / dV curve of the button-type battery made with the negative electrode active material of Comparative Example 1 does not show obvious characteristic peaks in the range of 0.4V to 0.5V, while the dQ / dV curves of the button-type batteries made with the negative electrode active materials of Examples 1 to 7 and Comparative Examples 2 to 4 show characteristic peaks in the range of 0.4V to 0.5V. For the negative electrode active material containing silicon crystals, the increase in the content of silicon crystals and the increase in the particle size of silicon crystals will promote to a certain extent the increase in the peak intensity of the characteristic peak in the range of 0.4V to 0.5V of the dQ / dV curve measured for the button-type battery. Comparative Example 2 uses flaky natural graphite with a relatively high silicon content as a raw material, and the negative electrode active material prepared therefrom has a relatively high gram capacity. However, due to the relatively high silicon content in the raw material, Si nanocrystals are easily aggregated and grown in the subsequent thermal reduction process, resulting in a relatively high peak intensity of the characteristic peak in the range of 0.4V to 0.5V measured by the button-type battery prepared using the negative electrode active material of Comparative Example 2. Comparative Example 3 uses flaky natural graphite with a relatively high silicon content as a raw material, and the negative electrode active material prepared therefrom has a relatively high gram capacity. In the process of preparing the negative electrode active material, the microwave rapid thermal treatment process used can avoid the growth of silicon grains to a certain extent. However, due to the high silicon content in the bulk phase, the characteristic peak intensity of the dQ / dV curve measured by the button-type battery prepared using the negative electrode active material of Comparative Example 3 in the range of 0.4V to 0.5V exceeds 600mAh·g -1 ·V -1 , which is also in the high range.
[0106] The characteristic peak intensity of the button-type batteries prepared by using the negative electrode active materials provided in Examples 1 to 7 and Comparative Example 4 in the range of 0.4V to 0.5V does not exceed 600mAh·g -1 ·V -1 However, since the silicon content in the negative electrode active material prepared in Comparative Example 4 is relatively low, the gram capacity measured for the negative electrode active material prepared in Comparative Example 4 is at a relatively low level, which is close to the gram capacity measured for the negative electrode active material prepared in Comparative Example 1.
[0107] Table 1. Button battery test results
[0108]
[0109]
[0110] Example 9
[0111] In this embodiment, the negative electrode active materials prepared in Examples 1 to 7 and Comparative Examples 1 to 4 are used to prepare lithium ion batteries in the following manner.
[0112] 1. Preparation of positive electrode
[0113] The positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), conductive agent acetylene black, and binder PVDF are mixed in a mass ratio of 96:2:2, and a solvent NMP is added to the resulting mixture, the resulting slurry is put into a vacuum mixer, and the slurry is stirred until the system is uniform under the action of the vacuum mixer to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on both surfaces of the positive electrode current collector aluminum foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain an NCM positive electrode sheet.
[0114] 2. Preparation of negative electrode
[0115] The negative electrode active materials for preparing lithium ion batteries provided in Examples 1 to 7 and Comparative Examples 1 to 4 are respectively mixed with a conductive agent acetylene black, a thickener CMC, and a binder SBR in a mass ratio of negative electrode active material: acetylene black: CMC: SBR = 96.4:1:1.2:1.4, and deionized water as a solvent is added to the resulting mixture, and the resulting slurry is put into a vacuum mixer, and the slurry is stirred until the system is uniform under the action of the vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on both surfaces of the negative electrode current collector copper foil, dried at room temperature, and then transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet.
[0116] 3. Preparation of Electrolyte
[0117] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent, and then fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent to prepare an electrolyte with a LiPF6 concentration of 1 mol / L.
[0118] 4. Selection of isolation film
[0119] A polyethylene film is used as the isolation film.
[0120] 5. Preparation of Lithium-ion Batteries
[0121] The negative electrode sheets using different negative electrode active materials prepared above and the NCM positive electrode sheets are respectively used as the positive and negative electrode sheet combination of the battery cell. The NCM positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive and negative electrode sheets to play an isolating role, and then wound to obtain a bare battery cell; the bare battery cell is placed in an outer packaging shell, and after all components are dried, the electrolyte is injected into the outer packaging shell, and after vacuum packaging, standing, forming, shaping and other processes, the NCM lithium-ion battery is obtained.
[0122] Test Example 2
[0123] 1. Test subjects
[0124] This test example uses the lithium-ion battery prepared in Example 9 as the test object.
[0125] 2. Test items
[0126] (1) Cyclic performance test:
[0127] At 25°C, the test object was subjected to a cycle test according to the following procedure: the test object was fully charged at a 1C rate, and fully discharged until the capacity of the test object was less than 80% of the initial capacity, and the number of cycles was recorded.
[0128] (2) DC impedance test:
[0129] At 25°C, the test object was charged to 50% SOC and discharged at a current rate of 1C for 18 seconds. The battery voltage U2, current I before discharge termination and battery voltage U1 after battery voltage stabilization were recorded. The DC internal resistance R was calculated according to the formula R = (U2-U1) / I. The DC internal resistance before and after the battery cycle was recorded as R0 and R1, respectively. The DC resistance change rate = (R1-R0) / R0.
[0130] 3. Test results
[0131] The test results of this test example are shown in Table 2. For the convenience of comparison, Table 2 also shows the first efficiency, gram capacity and dQ / dV curve test results of the negative electrode active material measured in Test Example 1.
[0132] From the test results, it can be seen that, in the case of the same positive electrode sheet, compared with the lithium ion batteries made of the negative electrode active materials provided in Comparative Examples 2 and 3, the lithium ion batteries made of the negative electrode active materials provided in Examples 1 to 7 have significantly more cycles and significantly lower DC impedance growth rates. Although the lithium ion batteries made of the negative electrode active materials provided in Comparative Examples 1 and 4 can also achieve a large number of cycles, the gram capacity corresponding to the negative electrode active materials made in Comparative Examples 1 and 4 is relatively low, lower than the theoretical gram capacity of graphite, while the gram capacity of the negative electrode active materials made in Examples 1 to 7 exceeds the theoretical gram capacity of graphite.
[0133] Combined with the test results of Test Example 1, it can be seen that the dQ / dV differential curves of the button-type batteries made using the negative electrode active materials of Comparative Examples 2 and 3 respectively have characteristic peak intensities exceeding 600 mAh·g in the range of 0.4V to 0.5V. -1 ·V -1 The negative electrode sheets made from the negative electrode active materials provided in the two comparative examples have poor structural stability. After undergoing cyclic charge and discharge, the negative electrode active coating of the negative electrode sheet is prone to breakage and pulverization. As a result, as the number of cycles increases, the lithium-ion battery using the negative electrode active materials of the two comparative examples has a significant decrease in capacity and an increase in DC impedance. The negative electrode active material provided in comparative example 2 is prone to lithium-generated amorphous LixSi phase during the charge and discharge cycle. The movement between the amorphous LixSi phase and the pure silicon phase interface is prone to cause silicon particles to break, and as lithium-ionization proceeds, the amorphous Li x Si y Transformed into crystalline phase Li 15 Si4 generates a large expansion stress. When the expansion stress acts on the graphite sheet, which has many pores, these pores easily become unstable sites for crack generation, aggravating the rupture of natural graphite, exposing the internal silicon particles and the inner surface of natural graphite to the electrolyte at the same time, causing material loss on the one hand, and on the other hand, the fresh interface constantly reacts with the electrolyte to consume active lithium, thereby reducing the cycle life of the battery. The silicon content of the negative electrode active material provided in Comparative Example 3 is too high, and it is also easy to generate Li during the charge and discharge cycle. 15 Si4 makes it easy for expansion stress to accumulate inside the negative electrode active material. As the number of cycles increases, the expansion stress intensifies and reaches a level that natural graphite particles cannot resist. The negative electrode active material particles will then break or even shatter, causing a cycle drop.
[0134] The characteristic peak intensity of the dQ / dV differential curves of the button-type batteries prepared using the negative electrode active materials of Examples 1 to 7 in the range of 0.4V to 0.5V does not exceed 600mAh·g -1 ·V -1 After undergoing charge and discharge cycle tests, the negative electrode sheets of these lithium-ion batteries can basically maintain their structure before the test, without obvious deformation, breakage, powder loss, etc., and have good structural stability, so that these lithium-ion batteries show good cycle characteristics. In Examples 1 to 6, the flaky natural graphite included in the raw materials for preparing the negative electrode active material contains a certain amount of silicon. Such flaky natural graphite is spheroidized to prepare a spherical precursor. The silicon contained in the flaky natural graphite is embedded in the internal lamellar structure of the spherical precursor as the flaky natural graphite curls and spheroidizes. Based on this, in the finished negative electrode active material, the silicon grains are embedded in the lamellar structure of the spherical natural graphite, and the amorphous carbon in the finished negative electrode active material forms an outer coating layer coated on the outside of the natural graphite. Therefore, when the negative electrode active material participates in the charge and discharge cycle of the lithium ion battery, the graphite around the silicon grains can have a certain binding effect on the expanded silicon grains, thereby preventing the expanded silicon grains from falling off the negative electrode active material, so that the lithium ion batteries made using the negative electrode active materials prepared in Examples 1 to 6 can achieve a high level of cycle times in the cycle characteristics test. Different from Examples 1 to 6, in Example 7, the flaky natural graphite with a silicon content of 0 is first spheroidized to obtain a spherical precursor with a silicon content of 0, and then the spherical precursor is mixed with nano-silicon particles to introduce silicon into the reactant system. Therefore, in the finished negative active material, as described above, the silicon grains are attached to the outer surface of the spherical natural graphite without entering its sheet structure. Since the silicon grains in the negative active material prepared in Example 7 are not restricted by the natural graphite sheets, compared with the negative active materials prepared in Examples 1 to 6, the silicon grains contained in the negative active material of Example 7 expand to a greater extent during the application process, and are more likely to fall off from the negative active material, resulting in poor cycle stability of the lithium ion battery prepared using the negative active material provided by Example 7, but it can still meet the application requirements. Furthermore, the peak intensity of the characteristic peaks of the button-type batteries prepared using the negative electrode active materials of Examples 1 to 3 in the range of 0.4V to 0.5V does not exceed 300mAh·g -1 ·V -1 Correspondingly, among the lithium-ion batteries tested, the lithium-ion batteries made from the negative electrode active materials of Examples 1 to 3 respectively measured a higher number of cycles and a lower DC impedance growth rate.
[0135] Table 2. Test results of lithium-ion batteries
[0136]
[0137] The above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit the protection scope of the present invention. Although the present invention is described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the technical solutions of the present invention can be modified or equivalently replaced, but these modifications or replacements are all within the protection scope of the present invention.
Claims
1. A negative electrode active material, characterized in that: The negative electrode active material comprises graphite and silicon grains, wherein the silicon content in the negative electrode active material is not less than 2500 ppm; in the voltage dQ / dV differential curve of the button battery made of the negative electrode active material, the peak intensity in the range of 0.4 to 0.5 V is less than 600 mAh·g -1 ·V -1 The voltage dQ / dV differential curve is obtained by placing the button battery on hold for 12 hours, discharging the button battery to 5 mV at a rate of 0.1C, placing it on hold for 10 minutes, then discharging the button battery to 5 mV at a rate of 0.05C, placing it on hold for 10 minutes, then discharging the button battery to 5 mV at a rate of 0.01C, placing it on hold for 10 minutes, then discharging the button battery to 5 mV at a current of 0.01mA, placing it on hold for 10 minutes, and finally charging the button battery to 2V at a constant current of 0.1C, placing it on hold for 10 minutes, and then repeating the above method for 5 cycles, and obtaining the voltage dQ / dV differential capacity curve from the charging curve of the 5th cycle.
2. The negative electrode active material according to claim 1, characterized in that: In the voltage dQ / dV differential curve, the peak intensity in the range of 0.4 to 0.5 V is less than 300 mAh·g -1 ·V -1 .
3. The negative electrode active material according to claim 1, characterized in that: The particle size of the silicon grains is less than 50 nm.
4. The negative electrode active material according to claim 3, characterized in that: The particle size of the silicon crystal grains is less than 25 nm.
5. The negative electrode active material according to claim 1, characterized in that: In the negative electrode active material, the silicon content is 2500 to 30000 ppm.
6. The negative electrode active material according to claim 5, characterized in that: In the negative electrode active material, the silicon content is 2500 to 15000 ppm.
7. The negative electrode active material according to claim 1, characterized in that: The graphite includes natural graphite.
8. The negative electrode active material according to claim 7, characterized in that: In the negative electrode active material, at least a portion of the silicon crystal grains are embedded in the interlayer structure of the graphite.
9. The negative electrode active material according to any one of claims 1 to 8, characterized in that: At a charging voltage of 5mV to 2V, the charging capacity of the negative electrode active material is >372mAh·g -1 .
10. A lithium ion battery, characterized in that: The invention comprises a positive electrode sheet and a negative electrode sheet, wherein the negative electrode active material layer of the negative electrode sheet contains the negative electrode active material as claimed in any one of claims 1 to 9.
Citation Information
Patent Citations
Negative electrode material, method for producing said negative electrode material, and mixed negative electrode material
CN110419130A
Negative plate and battery using same
CN116154104A